H i, FRB, What’s Your z: The First FRB Host Galaxy Redshift from Radio Observations - Glowacki, Marcin; Bera, Apurba; Lee-Waddell, Karen; Deller, A.T.; Dial, T.; Gourdji, K.; Simha, S.; Caleb, M.; Marnoch, L.; Prochaska, J.X.; Ryder, S.D.; Shannon, R.M.; et al. (2024)
Identification and follow-up observations of the host galaxies of fast radio bursts (FRBs) not only help us understand the environments in which the FRB progenitors reside, but also provide a unique way of probing the cosmological parameters using the dispersion measures (DMs) of FRBs and distances to their origin. A fundamental requirement is an accurate distance measurement to the FRB host galaxy, but for some sources viewed through the Galactic plane, optical/near-infrared spectroscopic redshifts are extremely difficult to obtain due to dust extinction. Here we report the first radio-based spectroscopic redshift measurement for an FRB host galaxy, through detection of its neutral hydrogen (H i) 21 cm emission using MeerKAT observations. We obtain an H i-based redshift of z = 0.0357 ± 0.0001 for the host galaxy of FRB 20230718A, an apparently nonrepeating FRB detected in the Commensal Real-time ASKAP Fast Transients survey and localized at a Galactic latitude of -0.°367. Our observations also reveal that the FRB host galaxy is interacting with a nearby companion, which is evident from the detection of an H i bridge connecting the two galaxies. A subsequent optical spectroscopic observation confirmed an FRB host galaxy redshift of 0.0359 ± 0.0004. This result demonstrates the value of H i to obtain redshifts of FRBs at low Galactic latitudes and redshifts. Such nearby FRBs whose DMs are dominated by the Milky Way can be used to characterize these components and thus better calibrate the remaining cosmological contribution to dispersion for more distant FRBs that provide a strong lever arm to examine the Macquart relation between cosmological DM and redshift.